2013
DOI: 10.5897/ajmr2013.6115
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and abundance of arbuscular mycorrhizal fungi associated with acacia trees from different land use systems in Ethiopia

Abstract: Root samples and rhizosphere soil of nine acacia species (Acacia abyssinica, Faidherbia albida, A. nilotica, A. senegal, A. seyal, A. sieberiana, A. saligna, A. tortilis and A. robusta) were collected from Bishoftu, Zeway and Addis Ababa sites with different land use types to assess their Arbuscular Mycorrhizal Fungal (AMF) diversity, spore density and root colonization. The percentage of root length colonized by AMF was estimated. Spores, spore clusters and sporocarps extracted from soil samples were counted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
20
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 47 publications
14
20
3
Order By: Relevance
“…Based on one-way ANOVA, the colonization of different AM structures varied greatly among plant species both within and between land-use types. AMF-colonization levels in agroforestry practices were higher compared to cropland, result supported by previous findings [24]; [25]; [26] in different parts of Ethiopia. Spore abundance was highest in land use with lower intensity (the culturally protected forest) and less abundant in more intense land uses (agroforest and cropland).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on one-way ANOVA, the colonization of different AM structures varied greatly among plant species both within and between land-use types. AMF-colonization levels in agroforestry practices were higher compared to cropland, result supported by previous findings [24]; [25]; [26] in different parts of Ethiopia. Spore abundance was highest in land use with lower intensity (the culturally protected forest) and less abundant in more intense land uses (agroforest and cropland).…”
Section: Discussionsupporting
confidence: 90%
“…In the agroforestry systems were detected 24 morphospecies. The forest had the highest number of morphospecies (26), and the least morphotypes were found in mono-cropping systems (21). The Shannon diversity index showed ranges from 1.92 in croplands to 2.1 in culturally protected forest and evenness was ranged from 0.33 (the smallest) in cropland, 0.34 in the forest land use and 0.36(the largest) in agroforestry practices, and Simpson's diversity index shows the highest value for cropland (0.0059), agroforestry (0.0046) and the lowest (0.0042) for the culturally protected forest (data not shown).…”
Section: Amf Spore Community Compositionmentioning
confidence: 99%
“…However, in this study, the influence of P was not recorded. In their study, Zerihun et al (2013) showed a significant negative correlation between AMF spore density and available P. These findings were similar to some reports from India and Northern Europe (Udaiyan et al, 1996;Kahiluoto et al, 2001). In contrast to this, Muleta et al (2007) observed a positive relationship between spore number and available P in soil samples from natural coffee forest in Ethiopia.…”
Section: And In Acacia Andsupporting
confidence: 81%
“…Different authors reported different findings from Ethiopian fungi (Alemu, 2013;Belay et al, 2013;Bitew, 2010;Gebregiorgis, 2015;Hailu et al, 2012;Megersa et al, 2017c;Sahile et al, 2011;Teklebirhan & Bitew, 2015;Yenealem et al, 2013). But there is no effort has been done to produce sugars from lignocellulosic wastes through fungal enzymes except characterizing the enzymes from wood rot fungi Megersa & Gure, 2018;Megersa et al, 2017aMegersa et al, , 2017b.…”
Section: Introductionmentioning
confidence: 97%